Uvedba zdravljenja kroničnih ran z ličinkami muh Lucilia sericata v Slovenijo - Jaklič, Domen (Zdravniški vestnik, 2008)
Background Due to infection of chronic wounds with antibiotic resistant bacterial strains, their healing can be very difficult. The main purpose of the presented research study was the introduction of a new method for chronic wounds healing, using Lucilia sericata fly larvae into Slovenia. Methods For chronic wound healing sterile larvae of L. sericata fly were prepared from a continuous fly culture, maintained at the Department of Biology, Biotechnical Faculty, University of Ljubljana. In this way 32 wounds of 30 patients were treated. Larvae were applied on the wounds for two to three days. Than they were washed off and replaced, if necessary. Microbiological smears were collected before and after the application of the larvae on the wounds. Microorganisms were then isolated and identified. During larval therapy healing improvement, patientćs general state, potential presence of pain, mobility, patientćs independence and psychological reaction to the therapy were monitored. Results Using biosurgical therapy 24 (75%) out of 32 wounds were cleaned and healed. In the case of combined arterio-venous leg ulcers onewound was completely healed and eight of them were cleaned of necrosis and infection. In the case of a venous leg ulcer, six diabetic ulcers, eight casesof chronic postoperative wounds and pressure ulcers, wounds were completely cleaned after the treatment. 16 patients reported unpleasant feeling during larval treatment and two patients felt pain which diminished after the treatment with analgesics. 17 (57%) patients had to use crutches during biosurgical treatment and the same number of patients felt uncomfortable, frightened and depressed during the application of larvae.
Keywords: bakterijske infekcije; biokirurgija; kronične rane; ličinke muh; rane; therapy; zdravljenje